Variants in SRY and NR5A1 Genes in Sri Lankan children with 46, XY disorders of sex development: insights into mutation spectrum and diagnostic potential - Daniel Sanjeev Ferdinands; Sumadee De Silva; Asanka Sudeshini Hewage; Navoda Atapattu (Egyptian Journal of Medical Human Genetics)
Abstract Background 46, XY disorders of sex development (DSD) are clinically and genetically heterogeneous congenital conditions caused by abnormal or incomplete gonadal, genital, or chromosomal development that results in discordant phenotypic sex. The pathophysiology of 46, XY DSD is influenced by genetic variations in sex development genes, including SNPs, indels, and CNVs. Twelve clinically confirmed children with 46, XY DSD and four healthy controls were selected for the current study. Direct sequencing was performed to detect potential genetic variants in exon 4 of NR5A1 (N = 12) and the single exon of the SRY (N = 10) genes. Additionally, nine patients (N = 9) were analysed for large deletions or duplications in the sex determination genes NR5A1, SRY, SOX9, NR0B1, and WNT4 using the multiple ligation probe amplification (MLPA) technique. Results One patient displayed ambiguous heterozygous duplications in exon 3 of WNT4 and in exons 4 and 6 of NR5A1, while another sample showed ambiguous heterozygous duplication within exon 3 of NR5A1. Two novel variants were detected during SNP analysis of the SRY gene: c.568A > C in 4 patients and c.(− 33 T > A) in 7 patients and all four healthy controls. According to in silico prediction, c.568A > C was classified as “benign”, whereas the 5′UTR variant (c.  −  33 T > A) appears non-pathogenic, given its presence in all healthy controls. In addition, previously reported silent variant c.393G > A was detected in exon 4 of NR5A1 in 5 patient samples. A missense variant, c.437G > C, was identified in exon 4 of the NR5A1 gene in one patient. As per in silico prediction, this variant was indicated as “benign”, although previous studies have suggested it may act as a disease modifier and susceptibility factor for micropenis and cryptorchidism. Conclusion This study contributes to defining the mutation spectrum of SRY and NR5A1 genes in 46, XY DSD in a cohort of patients in Sri Lanka. These findings may aid in developing genetic diagnostic tools for early diagnosis and improved clinical management. However, future research should focus on expanding the cohort size to improve the generalisability of these findings. Whole-exome sequencing can be used to identify genetic variants, which can be evaluated through functional studies to determine their biological impact.